Increased bio-toxicity of leachates from polyvinyl chloride microplastics during the photo-aging process in the presence of dissolved organic matter - Lei Chen; Hangyu Qi; Ke Yu; Buhong Gao (Water Science and Technology, 2023)
The pollution caused by microplastics (MPs) has gained global attention due to their potential risks to organisms and human health. The process of photo-aging, which plays a crucial role in the transformation of MPs in aquatic environments, has the potential to influence the ecological risk posed by these particles. Dissolved organic matter (DOM) is a prevalent photosensitizer in surface waters that has been shown to facilitate the transformation of various organic compounds by generating reactive oxygen species under light irradiation. The present study investigated the influence of humic acid (HA), a typical component of DOM, on the photo-aging process of polyvinyl chloride MPs (PVC-MPs), using Fourier transform infrared spectroscopy, as well as assessing the resulting ecological risk through bioassays. The results revealed that the presence of HA enhanced the photo-aging of PVC-MP. Moreover, the leachate exhibited higher acute and genetic toxicity under light irradiation when compared to dark conditions. Notably, the presence of HA significantly increased the toxicity of the leachate, emphasizing the need to consider the impact of DOM when assessing the ecological risk of MPs in surface waters. These findings contribute to a more comprehensive understanding of the potential risks associated with microplastic pollution in natural environments. HIGHLIGHTS PVC-MP leachates exhibited higher acute and genetic toxicity under irradiation in the presence of dissolved organic matter.; A bioassay provided a cost-effective means to assess the ecological risks posed.;